Differences in educational attainment between obese and non-obese Kuwaiti female university students. (2020) - Al Hammadi, Hanouf H.; Alaslawi, Hamad A.; Hewitt, Allan; Reilly, John J.
Abstract: Individuals with obesity tend to perform less well than their non-obese peers in tertiary education, but there is little evidence from non-Western countries and recent studies. The present study aimed to test whether academic attainment differed between female undergraduates with obesity (defined by body mass index (BMI)), and those who were non-obese in Kuwait, a country with very high obesity prevalence. In 400 female Kuwaiti first- and second-year Social Science students (mean age 18⋅0, sd 0⋅6 years), educational attainment was defined as the Grade Point Average (GPA) across all subjects (from 1⋅00 to 4⋅00). The mean GPA (2⋅51, sd 0⋅53) among students defined as obese by the BMI ( n 163) was significantly lower than among the students defined as non-obese by the BMI ( n 237; 2⋅80, sd 0⋅63; P < 0⋅001), and those defined as obese were more likely to be in the lowest quartile for the GPA (OR 3⋅03; 95% CI 1⋅90, 4⋅85), independent of socio-economic status. Similar differences were observed between students defined as having high versus normal body fatness. Female undergraduates in Kuwait with obesity have lower academic attainment than their non-obese peers, and universities should consider measures to mitigate reduced attainment among their female undergraduates.